2010
DOI: 10.1007/s11926-010-0142-x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors in the Treatment of Systemic Sclerosis: From Animal Models to Clinical Trials

Abstract: Efficient antifibrotic therapies are not available for patients with systemic sclerosis (SSc). This review summarizes the current preclinical and clinical evidence for imatinib and related tyrosine kinase inhibitors as potential antifibrotic therapies for SSc and other fibrotic diseases. In experimental models of SSc, imatinib, nilotinib, and dasatinib demonstrated strong antifibrotic effects. Imatinib not only prevented fibrosis in the bleomycin-induced model of dermal fibrosis and the tight skin mouse-1 mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The anti-fibrotic effects of TKI are also apparent in humans, prompting their use in clinical trials for systemic sclerosis or idiopathic pulmonary fibrosis [49], [50]. Therefore, we examined the effects of these TKI on the function of MLCs.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-fibrotic effects of TKI are also apparent in humans, prompting their use in clinical trials for systemic sclerosis or idiopathic pulmonary fibrosis [49], [50]. Therefore, we examined the effects of these TKI on the function of MLCs.…”
Section: Discussionmentioning
confidence: 99%
“…While the effect on PDGF-stimulated fibroblasts seems to be dependent on inhibition of PDGF-R, blockade of TGF- β fibrogenesis is hardly explained by inhibition of TGF- β receptors, which are serine-threonine kinases [150]. Nonetheless c-Abl, the primary target of Imatinib, turned out to be an important noncanonical mediator of TGF- β -induced fibrosis, which otherwise is mediated by the classical Smad pathway [151, 152]. Daniels et al [142] first demonstrated that fibroblasts respond to TGF- β by stimulating c-Abl kinase activity independently of Smad2/3 phosphorylation or PDGF-R activation.…”
Section: Rational For Using Tki In Cgvhdmentioning
confidence: 99%
“…Experience suggests that new antifibrotic treatments can interfere with other disease manifestations, particularly small-vessel vasculopathy associated with Raynaud's phenomenon and digital ulcers. For example, the clinical use of tyrosine kinase inhibitors in SSc seems to be limited by vascular side effects—in particular, massive peripheral oedema, which are far less prominent in the treatment of other diseases such as chronic myeloid leukaemia 22. Thus, optimal antifibrotic treatments for patients with SSc should effectively treat both, fibrosis and vascular disease or, at least, not cause worsening of the patients' vascular manifestations.…”
Section: Discussionmentioning
confidence: 99%